Building sustainability assessment : system SBTool PT - Mateus, Ricardo (2010)
The multidimensional concept of sustainable building is often related solely to environmental indicators although the social, economic and cultural indicators are of substantial importance. The weight of various indicators depends on the context of a building project and further, interpretation of the assessment results depends on the sustainability strategies of the society. The recent Portuguese research on the applicability of assessment methods developed abroad shows, that modifications are necessary and local factors are crucial for each indicator as such but also for their relative meaning. Assessment of sustainability of buildings involves several interrelated and partly contradictory aspects. The different methods give insights to basics and cause-consequences instead of clear-cut results. For this reason, the use of assessment results (scores, indexes and profiles) in decision-making presupposes transparency and clarity. Based on the case studies of building sustainability assessment using various tools, the environmental indicators were shown to be often of lesser importance than the other, soft ones. This paper aims to present a novel approach to develop building sustainability assessment and rating and contributes to the evolution of generic methodology and international understanding by introducing an approach to take the different dimensions of sustainability into account. This methodology is based in the adaptation of the international Sustainable Building Tool (SBToolT®) to the Portuguese’s environmental, societal and economy contexts. The scope of the methodology that is going to be presented (SBToolT®) is to assess the sustainability of existing, new and renovated buildings in the urban areas and especially in the Portuguese context. This new methodology is intended to foster the awareness of the Portuguese construction market stakeholders and to allow adequate policy implementation on sustainable construction.